(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Today, we are living in the era of developed science and technology in which human being has no utopia and generally human being now days, thinks logically and will not accept anything unless the results are beneficial, tangible, vivid and personal. In ancient times, ritual and magical practices were humanity’s crucial forms of health care. Vipassana (Buddhist meditation) is one of the India’s prehistoric meditative practices with the help of which Siddharth Gautama became the Buddha 2,500 years ago. Meaning of Vipassana is “Insight”, (Mindfulness meditation) and it is a Pali word. Though, human being is now living in the era of developed science and technology but at the same time world is facing serious problems which threaten all mankind. After the WWII, the Coronavirus Covid-19 outbreak has become the most devastated disaster for human and its socio-economic development in the world. It seems that only Vipassana meditation has the capacity to eradicate total sufferings of human being. Anicca (Impermance), Dukkha (suffering) and Anatta (non-substantiality) are the basic teachings of the Buddha which is the foundation of Vipassana meditation. It is said that change is the only constant thing in this universe and Crises such as the Covid-19 pandemic has proved it. Vipassana can provide an approach to live life with this constant change. Demands for unconventional forms of medicine have increasing day by day and it is being proving that there are numerous health benefits of Vipassana meditation. This paper briefly reviews the Vipassana (Buddhist meditation) and its benefits for human beings during this Covid-19 pandemic.